Digital Module with the SFBC Approach to Increase the Self Esteem of Cyberbullying Victims - Pertiwi, Yuliani; Karneli, Yeni (Journal of Educational, Health and Community Psychology, 2024)
Students who are victims of cyberbullying have problems with low self-esteem, feeling sad, angry, experiencing anxiety disorders, feeling lonely, lacking social adjustment and withdrawing from social interactions. This is because the victim receives bad messages and treatment from other people continuously which sometimes makes him feel useless. As a result, students become lazy about going to school and their academic achievement becomes lower. This research aims to analyze the condition of self-esteem of cyberbullying victims and produce a product in the form of a digital module using the SFBC approach to increase the self-esteem of cyberbullying victims which is valid and can be used by guidance and counseling teachers and counselors. This research is development research using a 4-D model. This research involved 35 vocational school students who were victims of cyberbullying for needs analysis. The research trial subjects consisted of 3 experts to test the suitability of the content and appearance of the digital module, 3 guidance counselors/counselors to test the usability. Research data were analyzed using descriptive statistical analysis and non-parametric analysis. The research results show that students who are victims of cyberbullying have very low self-esteem. The digital module with the SFBC approach to increase the self-esteem of cyberbullying victims is considered very feasible. The practicality test results of the digital module are in the very good category. It was concluded that the digital module prepared was very suitable for implementation or use by guidance and counseling teachers and counselors. The implication of this research is that the digital module developed will help guidance and counseling teachers and counselors in providing services to victims of cyberbullying. Keywords: Digital Module, SFBC, Self Esteem, Cyberbullying